Alpha thalassaemia and the macular vasculature in homozygous sickle cell disease. - Condon, P I (1983)
The interaction of homozygous alpha thalassaemia 2 with homozygous sickle cell (SS) disease results in a generally milder haematological picture with less intravascular sickling, less haemolysis, and higher haemoglobin levels. Clinically, patients are generally more mildly affected, though not all vaso-occlusive complications are reduced. Thus there is a possibility that the advantages gained by inhibition of sickling have been offset by the rheological disadvantages of the higher haemoglobin level. The capillary bed in the perimacular region of the posterior pole has been used to examine the degree of vaso-occlusion in age and sex matched controls with SS disease with and without homozygous alpha thalassaemia 2. The results demonstrated significantly less capillary abnormalities in the perimacular region of patients with alpha thalassaemia, though the size of the foveal avascular zone and the grading of perimacular capillary drop-out did not differ between the 2 genotypes. These results are compatible with a mild inhibitory effect of alpha thalassaemia on vaso-occlusion of the macular vasculature in SS disease.